Pendampingan Guru Madrasah Ibtidaiyah dalam Mengimplementasikan Pembelajaran dan Asesmen Kurikulum Merdeka Menuju Madrasah Mandiri Berprestasi - Nur Hakim; Suheri Widianto; Muhammad Nur Hasan (GUYUB: Journal of Community Engagement, 2024)
The Merdeka Curriculum is a new curriculum aimed at improving the quality of education through a holistic approach, emphasizing the development of character, creativity, and multiple-intelligence of students. However, the implementation of the Merdeka Curriculum in Lamongan Regency faced several challenges, one of which was the limited understanding of teachers regarding the concepts and learning methodologies contained in the curriculum. To address these challenges, mentoring was provided to Madrasah IbtidaiyahI (Islamic Elementary School) teachers (a case study in Brondong Subdistrict, Lamongan). In this mentoring program, the subject of PKM (Community Service Program) was the teachers in 35 Madrasah Ibtidaiyah (MI) under the Working Group of Madrasah Ibtidaiyah (KKMI) in Brondong Subdistrict, Lamongan Regency. The assets (figuratively speaking) as the implementers of this program totaled 70 teachers, with two representatives from each madrasah. The mentoring method used the Asset Based Community Development (ABCD) approach, aiming to maximize the assets and potential of the madrasah, while involving active participation from all teachers. The mentoring results showed a significant increase in teachers' understanding of the Merdeka Curriculum, reaching 71.43%. Teachers were also able to develop lesson plans that align with the principles of flexibility and contextualization, and implement active learning methods through practical activities reinforcing the Pancasila Student Profile Project and the Rahmatan lil Alamin Student Profile (P5-PPRA). This mentoring provided benefits and positive outcomes for the madrasah and students. The madrasah became more independent and achieved better performance, while students obtained higher-quality and more meaningful learning experiences.